Data Privacy Management and Autonomous Spontaneus Security 6th International Workshop, DPM 2011, and 4th International Workshop, SETOP 2011, Leuven, Belgium, September 15-16, 2011, Revised Selected Papers - Garcia-Alfaro, Joaquin; Navarro-Arribas, Guillermo; Cuppens-Boulahia, Nora.; Capitani di Vimercati, Sabrina; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed joint post proceedings of two international workshops, the 6th International Workshop on Data Privacy Management, DPM 2011, and the 4th International Workshop on Autonomous and Spontaneous Security, SETOP 2011, held in Leuven, Belgium, in September 2011. The volume contains 9 full papers and 1 short paper from the DPM workshop and 9 full papers and 2 short papers from the SETOP workshop, as well as the keynote paper. The contributions from DPM cover topics from location privacy, privacy-based metering and billing, record linkage, policy-based privacy, application of data privacy in recommendation systems, privacy considerations in user profiles, in RFID, in network monitoring, in transactions protocols, in usage control, and in customer data. The topics of the SETOP contributions are access control, policy derivation, requirements engineering, verification of service-oriented-architectures, query and data privacy, policy delegation and service orchestration.
Keywords: Computer science; Computer Communication Networks; Operating systems (Computers).; Data encryption (Computer science).; Information Systems; Computer Science; Management of Computing and Information Systems; Data Encryption; Computers and Society; Computer Communication Networks; Operating Systems; Information Systems Applications (incl. Internet).